Os possíveis efeitos do uso dos dispositivos móveis por adolescentes: análise de atores de uma escola pública e uma privada - Kobs, Fabio Fernando (2017)
This research had as general objective to raise the possible effects using the mobile devices by adolescents mainly in family life and learning. It was developed in a group of students, parents and teachers of two high schools, one public, located in Curitiba, Paraná state, and another private, located in the city of São Bento do Sul, Santa Catarina state. To carry out the study, the specific objectives were: i) to get up the probable benefits and the probable risks arising from the use of mobile devices; ii) investigate the variables with the potential to alter the adolescents' life in the family and school; and iii) analyze the possible effect of mobile devices on adolescents, considering their family life and school performance. The research, as to the nature and the practical purpose, was descriptive, and from the point of view of its purpose, was predominantly explanatory; the study used the conception of the survey in the form of approach of the problem, and the methodology used for the Treatment was of mixed methods. The research employed stratified sampling and intentional sampling; and for each stratum the simple random sampling was used. The application of the questionnaires in the public high school was for 85 students, 24 parents and 9 teachers; and the private high school went to 76, 26 and 11 respectively. The study indicated that the effects of mediation of mobile devices largely converge on certain negative aspects rather than on positive aspects. The main benefits were: use for research; leisure; communication; video lesson learning; access to information and sharing of educational content. Particularly about the risks arising from the intensity and the way in which mobile devices are used, such as the tendency of the devices to arouse the sedentary lifestyle and the risks related to health especially of adolescents, related to posture, vision, hearing and sleep. In addition, there are risks with the radiation emitted by the mobile devices and with the incorrect discard of the mobile devices in disuse. Still, the study pointed out that a greater use of mobile devices, it was reflected in a slight reduction in the grade, motivated by the poor use of devices in the teaching-learning process.